Peningkatan Hasil Bawang Merah dan Perubahan Sifat Kimia Tanah dengan Pemupukan Berimbang Semi Organik pada Tanah Inceptisol - A.A. NYOMAN SUPADMA; I MADE DANA; I DEWA MADE ARTHAGAMA (Agrotrop : Journal on Agriculture Science, 2020)
Increased Yields Onion Plant and Changes of Soil Chemical Properties with Semiorganic Fertilization on Inceptisol Soil Tabanan. Thisexperiment to study the effects of inorganic fertilizer (P) and organic fertilizer (K) on the chemical properties as well as onion yields. A Factorial Randomized Block Design pot Experiment was conducted under Inceptisol soil conditions located at Kerambitan District, Tabanan Regency. The inorganic treatments consisted of P0 (control), P1 (50kg Phonska ha-1 + 200 kg ZA ha-1), P2 (100 kg Phonska ha-1 + 150 kg ZA ha-1), P3 (150 kg Phonska ha-1 + 100 kg.ZA ha-1). The organic treatments consisted of K0 (control), K1 (2 tons ha-1), K2 (4 tons ha-1), K3 (6 tons ha-1). Plant parameters observed including: plant height (cm), maximum number of leaves, maximum number of tubers, fresh and oven dry weight of tubers and hypothetical tubers fresh yields. The observed chemical soil properties including: soil pH and CEC. All data were analyzed using variance analysis and Duncan's test (0.05). The results showed that all fertilization treatments have significant effects on most parameters observed except plant height, soil pH and CEC. The P2K2 (100 kg Phonska ha-1 + 150 kg ZA ha-1) and (4 tons ha-1) treatment resulted in the best effects on the number tubers (7.7 tubers), weight of fresh tubers (37.9 g), tubers dry weight (6.5 g) per pot respectively. The highest hypothetical yields (9.5 tons ha-1) were also found under this treatment as well as the highest soil pH (6.6) and CEC (46.8 me 100g-1 of soil).